Spin N’go board game for employment income / Fatimah Alwi1 ... [et al.] - Alwi, Fatimah; Mansor, Norul Akma; Shamsudin, Siti Marlia; Baharom, Dr. Shahrel Nizar; Mohamed Khalil, Mohammad Izzat (2020)
Traditional teaching-learning process may cause students to be passive during classes. Over time, the teaching and learning process need to incorporate the interactive elements and methodologies. The purpose is to encourage peer-to-peer-discussion and to develop problem-solving skills. Many previous researches report positive outcomes from the usage of game-based learning among tertiary education students. Therefore, a board game named as Spin N Go Board Game is designed to attain these aims. This game will be used in taxation class, specifically for the topic of Employment Income. A framework known as the Serious Game Design Assessment Framework (SGDA Framework) developed by Mitgutsch and Alvarado (2012) is used as a reference in the development of Spin N Go Board Game. It contains six domains which are purpose, content, framing, mechanic, fiction/narrative and aesthetic/graphics. It is believed that by using this board game, students will gain more knowledge in this topic due to enhanced engagement and motivation in their studies. Additionally, the same outcome may also be achieved as students ought to learn Employment Income in a fun way and at their own pace.